A high-performance metal-free hydrogen-evolution reaction electrocatalyst from bacterium derived carbon1. Issue 14 (14th April 2015) - Wei, Li; Karahan, Huseyin Enis; Goh, Kunli; Jiang, Wenchao; Yu, Dingshan; Birer, Özgür; Jiang, Rongrong; Chen, Yuan
<x xml:space="preserve">Abstract</x> Nitrogen and phosphorus dual-doped mesoporous carbon derived from bacteria as a high performance electrocatalyst for the hydrogen evolution reaction.